United Kingdom : Financial Sector Assessment Program-Vulnerabilities in NBFIs, Market-Based Finance, and Systemic Liquidity. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2022)
The Financial Sector Assessment Program (FSAP) carried out a focused review of the non-banks in the United Kingdom and systemic liquidity. It reviewed five areas: (i) The overall NBFI system, its links to banks and the rest of the world; (ii) NBFI direct lending to the U.K. economy; (iii) Sterling investment funds (OEFs, AIFs, and MMFs); (iv) CCPs; and (v) Systemic liquidity. The NBFIs are defined as all non-deposit-taking corporations, listed in Figure 1, and with the following limited coverage: Pension Funds and Insurance Companies are covered to the extend they lend to the economy and interact with CCPs; Investment funds only to the extent of Sterling Funds; and broker-dealers only to the extent they interact with CCPs. Regulatory aspects of NBFIs are covered in a parallel Technical Note (TN).
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy; Money and Monetary Policy